2015
DOI: 10.1016/s0924-9338(15)32032-0
|View full text |Cite
|
Sign up to set email alerts
|

The “revolving Door Phenomenon” in an Acute Psychiatric Ward: a 5-year Retrospective Analysis

Abstract: IntroductionThe term ‘revolving door (RD) phenomenon” was coined to define recurrent hospitalizations of chronically ill patients after closure of psychiatric hospitals and implementation of community treatments.ObjectivesContinued readmissions require a large portion of Mental Health Departments’ resources.AimsTo analyze the RD phenomenon in an acute psychiatric ward during a 5-year period.MethodsWe retrospectively selected all patients with 3 or more hospitalizations per year from 01/01/ 2009 to 31/12/2013 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…In Italy, the Revolving Door phenomenon was analysed by very few studies (Barbato, Terzian, Saraceno, Montero Barquero, & Tognoni, 1992) that attempted to frame it within the complexity of changes introduced by the 1978 mental health reform act in Italian psychiatric services (Amaddeo & Barbui, 2018). Recent evidence (Di Lorenzo, Sagona, Landi, et al, 2016) of a higher revolving rate for personality disorders and manic episodes is not confirmed in our study. Such discrepancy further outlines the need for shared criteria to define the revolving door phenomenon and its systematic use across the studies.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In Italy, the Revolving Door phenomenon was analysed by very few studies (Barbato, Terzian, Saraceno, Montero Barquero, & Tognoni, 1992) that attempted to frame it within the complexity of changes introduced by the 1978 mental health reform act in Italian psychiatric services (Amaddeo & Barbui, 2018). Recent evidence (Di Lorenzo, Sagona, Landi, et al, 2016) of a higher revolving rate for personality disorders and manic episodes is not confirmed in our study. Such discrepancy further outlines the need for shared criteria to define the revolving door phenomenon and its systematic use across the studies.…”
Section: Discussioncontrasting
confidence: 98%
“…Gender and nationality were not found to influence RD, neither on the whole sample nor performing the analysis on each diagnostic cluster. Indeed, gender has not been found to influence length of stay (Dimitri et al, 2018) nor Revolving Door in other studies (Haywood et al, 1995) and the lack of association reported here is also in line with a recent study from a similar mental healthcare setting (Di Lorenzo et al, 2016…”
Section: Revolving Door Phenomenonsupporting
confidence: 93%
See 1 more Smart Citation
“…This, too, is in accordance with the literature on revolving-door patients. [3][4][5][6][7] Our finding with regard to ethnicity requires some deliberation. Although one would expect ethnicity other than that of the majority group to be associated with a higher risk of repeated ECPA, 16 it was clear from the regional differences that ethnicity was important mainly in Amsterdam.…”
Section: Resultsmentioning
confidence: 79%
“…Most of the little research that has been done on 'revolving-door' patients has focused on voluntary admissions. [3][4][5][6][7] It found four predictors of frequent readmissions: a history of previous psychiatric admissions, a diagnosis on the psychosis spectrum, being unemployed and living in residential accommodation. But few studies have investigated the prevalence of repeated compulsory psychiatric admissions and their risk factors.…”
Section: Introductionmentioning
confidence: 99%